CLINICAL DIAGNOSTIC VALUE OF OBSCURE ELECTROENCEPHALOGRAPHIC PATTERN "BROAD SHARP WAVE" IN CHILDREN - I. G. Kovalev; I. L. Stepanishhev; V. P. Zykov; T. A. Voronina (Эпилепсия и пароксизмальные состояния, 2016)
Interpreting of electroencephalographic (EEG) elements in patients with epileptic and non-epileptic seizures, neurological complaints, is still a subject of debates until this day. Broad sharp waves (BSW) are rarely recognizable EEG pattern, not applicated, currently in an international directory of clinical electroencephalography. The aim of our study was the primary, a retrospective survey of pediatric patients (3 to 18 years) to confirm or to refute the data that plays a pattern BSW has the predictive value for the detection of epilepsy, and that it can be named as independent pattern in the EEG references. Matherials and methods. There were made 244 routine electroencephalography in length from 15 to 40 minutes for children aged 3 to 18 years from March 2013 to March 2014. That children were the patients of Psychoneurology department in Toushinskaya Childhood City Hospital, study was conducted at the child in a state of restful alertness of the patient and included the routine recording and three functional tests: a test with a closingopening eye; photostimulation and hyperventilation for three minutes. Data were analyzed retrospectively, and included the collection of these data – age, sex of the child, the type of dominant EEG rhythm, frequency of the alpha rhythm, guides and complaints diagnoses at admission, the presence of one or another of epileptic activity on the EEG localization of pathological elements on EEG, changes in the imaging, neurological clinic patient complaints. Results. Broad sharp wave pattern (BSW) was detected in 31 (12.7%) patient's routine EEG of 244 collected during the calendar year. BSWs were localized in the fronto-temporal region in 12 cases, in 12 cases – in the fronto-central region. Wherein – at least in 7 (22.6%) out of 31 cases were found changes during neuroimaging of the brain of the patient. In 6 cases, the admission of the child was developed by a generalized tonic or tonic-clonic seizure, in 4 cases – there were not attacks – there were routine EEGs, in 1 case – a simple dialeptic attack. Conclusions. It can be presumed that the BSW – specific focal pattern registrering in the EEG in patients, mainly with complaints of epileptic character, in anamnaesis morbie, the predominantly observed generalized clonic-tonic and / or tonic seizures. Quite often, during neuroimaging at these patients there have been revealed various changes. The BSWs is mainly characteristic of the frontal, frontotemporal or fronto-central regions. Thus, the pattern stitch is likely to play a predictive value for the detection of epilepsy, as an indicator of acute and / or remote brain damage. Pattern BSW requires further study, the randomized treatment and cross-sectional studies of patients and in the future may be may be recognized as an independent pattern.